Aeschylus : Suppliants - Papadopoulou, Thalia, 1971- (Companions to Greek and Roman tragedy., 2011)
Aeschylus' 'Suppliants' dramatises the myth of the fifty daughters of Danaos, who flee Egypt and come to Argos as suppliants, trying to escape forced marriage to their Egyptian cousins. It was long considered to be the earliest surviving tragedy. Even after the mid-20th century, when new evidence established a later date for the play, critics tended to condemn it for its alleged 'archaic' features. As a result it has long been underestimated, although a careful examination reveals it to be one of the most exciting tragedies. This companion employs a variety of critical approaches to set the pl.